TECHNOLOGIES FOR DEVELOPING WRITING SKILLS THROUGH GAMIFICATION (Ustozlar uchun, 2025)
The integration of gamification technologies into writing instruction has shown potential in enhancing learner motivation and improving writing skills. This study investigates the current digital technologies and platforms employing gamification techniques aimed at developing writing proficiency. Using a mixed-methods approach involving a systematic literature review and interviews with educators, this research identifies key gamification elements utilized in writing tools and evaluates their impact on learner engagement and writing outcomes.